A cavity-reduced prefusion RSV F bivalent vaccine elicits durable and protective immunity - Lijie Liu; Mengrong Yan; Ruoxu Liang; Qingxin Wu; Changbin Qu; Huiqi Wu; Zhi Liao; Huiyu Chen; Jingjing Zou; Zeyun Sun; Dongyu Niu; Liyuan Wu; et al. (EMBO Molecular Medicine, 2026)
Abstract Respiratory syncytial virus (RSV) remains a major cause of severe respiratory disease, and stabilization of the prefusion (preF) conformation of the F glycoprotein is central for vaccine development. Here, we report a structure-guided engineering strategy that enhances preF stability by reducing the hydrophobic cavity within the trimeric F protein. Targeted modifications at metastability-associated sites generated RVF-88, a disulfide-free stabilized preF immunogen that preserves key neutralizing epitopes, including antigenic site Ø, while exhibiting improved structural integrity and long-term storage stability. Formulated as an unadjuvanted bivalent vaccine, RVF-88 elicited potent neutralizing antibody responses and durable immune protection lasting up to 5 months in mice. Vaccination also protected both mice and cotton rats against RSV challenge. Structural analyses confirmed the intended cavity-reduction design, revealing a reduced apical hydrophobic cavity volume and surface area while maintaining the prefusion architecture. Together, these findings establish hydrophobic cavity reduction as a rational strategy for stabilizing prefusion RSV F and provide a promising next-generation vaccine candidate with improved stability and immunogenicity for further clinical development.